Taxonomic changes in Cleveaceae (Marchantiidae, Marchantiophyta)—a correction - Long, David G.; Crandall-Stotler, Barbara J. (Phytotaxa, 2016)
The recently published combination Clevea nana (Lindenb.) Crand.-Stotl. & D.G.Long, which was intended to replace the name Clevea hyalina (Sommerf.) Lindb. on the basis of nomenclatural priority, is a later homonym of Clevea nana (Shimizu & S.Hatt.) Borovichev & Bakalin published in 2013 for a different taxon. Consequently, the name Clevea hyalina is the correct name for the widespread dioicous member of the genus. The heterotypic name Clevea nana (Shimizu & S.Hatt.) Borovichev & Bakalin refers to a different monoicous species of the genus that had previously been placed in synonymy of Clevea pusilla (Steph.) Rubasinghe & D.G.Long.